A lidar for detecting atmospheric turbulence based on modified Von Karman turbulence power spectrum - Zhou, Longxia; Mao, Jiandong (Frontiers in Physics, 2024)
Introduction: Atmospheric turbulence is a kind of random vortex motion. A series of turbulent effects, such as fluctuation of light intensity, occur when laser is transmitted in atmospheric turbulence. Methods: In order to verify the possibility of detecting atmospheric turbulence by the Mie-scattering lidar, firstly, based on the power spectrum method, the Zernike polynomial method is used to simulate generation of the modified Von Karman turbulent phase screen by low-frequency compensation. By comparing the obtained phase structure function with the theoretical value, the accuracy of the method is verified. Moreover, the transmission process of the Gaussian beam from Mie-scattering lidar through the phase screen is simulated, and the transmission characteristics of the beam under modified Von Karman turbulence are obtained by analyzing the fluctuation of light intensity. Secondly, based on the guidance for simulation analysis, a Miescattering lidar system for detecting the intensity of atmospheric turbulence was developed in Yinchuan area, and the atmospheric turbulence profile was inverted by detected scintillation index. Results: The results show it is feasible to use the Zernike polynomial method perform the low-frequency compensation, and the compensation effect of low order is better than that of high order compensation. The scintillation index of simulation is consistent with the actual detection result, and has the very high accuracy, indicating that the atmospheric turbulence detection using Mie-scattering lidar is effective. Conclusion: These simulations and experiments play a significant guiding role for the similar lidar to detect atmospheric turbulence.